The pathology of pericarditis. Issue 4 (April 2022) - Sathirareuangchai, Sakda; Armstrong, Susan
Abstract: Pericarditis is the most common pericardial disease. Clinically, pericarditis can be categorized into acute, incessant, chronic, and recurrent pericarditis based on the onset and duration of signs and symptoms. Constrictive pericarditis is a separate entity with different clinical manifestations and pathophysiology. The risk of developing constrictive pericarditis depends on the underlying cause. The etiologies of pericarditis are diverse, ranging from infection, autoimmune/autoinflammatory diseases, malignancy, post-cardiac injury syndrome, and idiopathic. Pathologic morphology of pericarditis can be categorized into fibrinous, purulent, chronic fibrosing, hemorrhagic, and cholesterol pericarditis. Even though the majority of cases of pericarditis are idiopathic, pericarditis identified during autopsy tends to have identifiable causes. Pathologists should focus on past medical history, pericardial morphology, and overall autopsy findings when approaching pericarditis at autopsy.